A Molecular atlas of Xenopus respiratory system development. Issue 1 (11th September 2014) - Rankin, Scott A.; Thi Tran, Hong; Wlizla, Marcin; Mancini, Pamela; Shifley, Emily T.; Bloor, Sean D.; Han, Lu; Vleminckx, Kris; Wert, Susan E.; Zorn, Aaron M.
<x xml:space="preserve">Abstract</x> Background: Respiratory system development is regulated by a complex series of endoderm–mesoderm interactions that are not fully understood. Recently Xenopus has emerged as an alternative model to investigate early respiratory system development, but the extent to which the morphogenesis and molecular pathways involved are conserved between Xenopus and mammals has not been systematically documented. Results: In this study, we provide a histological and molecular atlas of Xenopus respiratory system development, focusing on Nkx2.1+ respiratory cell fate specification in the developing foregut. We document the expression patterns of Wnt/β‐catenin, fibroblast growth factor (FGF), and bone morphogenetic protein (BMP) signaling components in the foregut and show that the molecular mechanisms of respiratory lineage induction are remarkably conserved between Xenopus and mice. Finally, using several functional experiments we refine the epistatic relationships among FGF, Wnt, and BMP signaling in early Xenopus respiratory system development. Conclusions: We demonstrate that Xenopus trachea and lung development, before metamorphosis, is comparable at the cellular and molecular levels to embryonic stages of mouse respiratory system development between embryonic days 8.5 and 10.5. This molecular atlas provides a fundamental starting point for further studies using Xenopus as a model to define the conserved genetic programs controlling early respiratory system development. Developmental Dynamics 244:69–85, 2015. © 2014 Wiley Periodicals, Inc.